Transient Stability Enhancement of Multimachine Power System Using Robust and Novel Controller Based CSC-STATCOM. (4th February 2015) - Gupta, Sandeep; Tripathi, Ramesh Kumar
Abstract : A current source converter (CSC) based static synchronous compensator (STATCOM) is a shunt flexible AC transmission system (FACTS) device, which has a vital role as a stability support for small and large transient instability in an interconnected power network. This paper investigates the impact of a novel and robust pole-shifting controller for CSC-STATCOM to improve the transient stability of the multimachine power system. The proposed algorithm utilizes CSC based STATCOM to supply reactive power to the test system to maintain the transient stability in the event of severe contingency. Firstly, modeling and pole-shifting controller design for CSC based STATCOM are stated. After that, we show the impact of the proposed method in the multimachine power system with different disturbances. Here, applicability of the proposed scheme is demonstrated through simulation in MATLAB and the simulation results show an improvement in the transient stability of multimachine power system with CSC-STATCOM. Also clearly shown, the robustness and effectiveness of CSC-STATCOM are better rather than other shunt FACTS devices (SVC and VSC-STATCOM) by comparing the results in this paper.